Progress in Achieving Sustainable Industrial Development - the Case of the Czech Republic and Poland - Marta Ulbrych (Comparative Economic Research. Central and Eastern Europe, 2020)
The aim of this paper is to clarify the concept of sustainable industrial development and present the results of a study on the progress in achieving goals in this field adopt- ed by the United Nations (UN) in 2015. The research covered the Czech and Polish economies in the period 2000-2018. Under the United Nations 2030 Agenda for Sustainable Development, the need to promote inclusive and sustainable industrialisation was identified. In the context of sustainable industrial development, it is emphasised that it should encourage a competitive economy, create employment, and protect the environment by efficiently utilising non-renewable resources. To assess this phenomenon in the analysed economies, indicators identified by the UN under SDG9 were used.
Keywords: L50; O14; Q50; 330; green industrial policy; sustainable development goals; SDG 9; sustainable industrial development